2018
DOI: 10.1080/19376812.2018.1485585
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics in agricultural systems in Chad

Abstract: Changes to agricultural systems in Sub-Saharan Africa are subject to a wide range of drivers, often resulting in rapid and nonlinear dynamics. Such dynamics are however rarely recognized in studies of trends and drivers, which usually rely on assumptions of gradual progressions, and often using highly aggregated data. This paper addresses this lack of recognition and understanding of nonlinear processes in agricultural systems in Sub-Saharan Africa by statistically identifying breakpoints and trends in regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The patterns of change in regional agricultural production in Chad have been analyzed by Nilsson and Uvo (2018), who found that 83% of the increases in production for the period 1990-2016 can be explained by expansions in harvested area. They also emphasized the importance of distinguishing between abrupt and gradual changes in the agricultural production over this time period, as they found that 80% of the increase in harvested area and 89% of the increase in yield in the Sahelian zone in Chad 1 were due to abrupt changes, i.e., changes occurring at a single year with a statistically detectable lasting effect (see "Agriculture" section).…”
Section: Agricultural Systems In Chadmentioning
confidence: 99%
See 4 more Smart Citations
“…The patterns of change in regional agricultural production in Chad have been analyzed by Nilsson and Uvo (2018), who found that 83% of the increases in production for the period 1990-2016 can be explained by expansions in harvested area. They also emphasized the importance of distinguishing between abrupt and gradual changes in the agricultural production over this time period, as they found that 80% of the increase in harvested area and 89% of the increase in yield in the Sahelian zone in Chad 1 were due to abrupt changes, i.e., changes occurring at a single year with a statistically detectable lasting effect (see "Agriculture" section).…”
Section: Agricultural Systems In Chadmentioning
confidence: 99%
“…Migration is a key feature in demographic change, and is likely to differ considerably between regions, considering different employment opportunities, security threats, and family connections. Nilsson and Uvo (2018) compared growth rates in total and agricultural population to growth in agricultural output for regions in the Sahelian and Soudanian zones in Chad, and found evidence of linear relationships, indicating that both the harvested areas and the yields grow partly in response to population driven demand and labor availability in the respective regions.…”
Section: Agricultural Systems In Chadmentioning
confidence: 99%
See 3 more Smart Citations